2012
DOI: 10.2967/jnumed.111.100883
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics and Reproducibility of 18F-Sodium Fluoride for Oncology Using Current PET Camera Technology

Abstract: We evaluated the kinetics of 18F-sodium fluoride (NaF) and reassessed the recommended dose, optimal uptake period, and reproducibility using a current-generation PET/CT scanner. Methods In this prospective study, 73 patients (31 patients with multiple myeloma or myeloma precursor disease and 42 with prostate cancer) were injected with a mean administered dose of 141 MBq of 18F-NaF. Sixty patients underwent 3 sequential sessions of 3-dimensional PET/CT of the torso beginning ~15 min after 18F-NaF injection, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
82
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 13 publications
2
82
3
Order By: Relevance
“…These results have been previously reported (15). The secondary objective of the study, as reported here, was to assess changes in Na 18 F over time and their ability to predict clinical outcomes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These results have been previously reported (15). The secondary objective of the study, as reported here, was to assess changes in Na 18 F over time and their ability to predict clinical outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have evaluated the ability of Na 18 F PET/CT to detect bone metastases compared with other nuclear and radiologic modalities, with highly favorable results for Na 18 F PET/CT (7)(8)(9)(10)(11)(12)(13)21,22). Na 18 F PET/CT demonstrated high reproducibility in a prospective study of dual baseline scans in patients with prostate cancer and multiple myeloma (15), supporting its clinical value in oncology practice. Still, many clinicians are reluctant to embrace Na 18 F PET/CT as it is unclear whether it is overly sensitive and thus does not accurately represent disease status.…”
Section: Discussionmentioning
confidence: 99%
“…Radiolabeled sodium fluoride, 18 F-NaF, was first introduced by Blau et al in 1972 (3) for the detection of bone lesions with PET. However, 18 F-NaF was largely replaced by bone scintigraphy using 99m Tc because of superior imaging characteristics with conventional g-cameras and the readily available supply of 99m Tc (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…However, 18 F-NaF was largely replaced by bone scintigraphy using 99m Tc because of superior imaging characteristics with conventional g-cameras and the readily available supply of 99m Tc (3)(4)(5)(6). With recent technologic advances in PET, 18 F-NaF PET has been increasingly used for detecting bone metastases because of its higher specificity and sensitivity as compared with planar bone scintigraphy and SPECT (4,5,(7)(8)(9)(10).…”
mentioning
confidence: 99%
See 1 more Smart Citation